Two new species of Petalophthalmus and Ipirophthalmus (Crustacea: Mysida: Petalophthalmidae), from New Zealand - Forman, Jeffrey S.; Schnabel, Kareen E. (Zootaxa, 2021)
Two new deep-water mysids from the subfamily Petalophthalminae (Crustacea: Mysida: Petalophthalmidae) are described from specimens collected from Challenger Plateau, Chatham Rise, and off the east coast of the North Island of New Zealand. These new species raise the number of species of both genera to five. Petalophthalmus lobatus sp. nov. differs from its congeners by the structure of an elongated ventilation lobe on the seventh oostegites, laterally flattened eyes, and the armature of the telson. Ipirophthalmus crusulus sp. nov. can easily be distinguished by the rudimentary sixth to eighth thoracic endopods. Both species were found to be the prey of several fishes, including commercially caught species, providing insight into their ecology. An identification key to the subfamily is provided.